Wind tunnel study of wind loads on a tennis stadium open roof - Marañón Di Leo, Julio (2015)
This paper aims to show the wind tunnel study of a roof for a tennis stadium, composed of a fixed and a sliding part. The need for this study is originated in the absence of information in the Argentinian codes for this type of roofs and the importance of a concrete knowledge of the wind effects on it for the determination of design loads on the involved structures. The results show a significant variability of loads, as expected, at different opening conditions of the sliding roof.